Contract Documentation and Education Sector Service Delivery in Masaka District Local Government, Uganda. - Nduhura, Twesigye; Kanyamasoro, Muhire; Kiiza, Mark; Nakalanzi, Beatrice Juliet (International Journal of Academic and Applied Research (IJAAR), 2022)
This study explored the relationship between contract documentation and education sector service delivery in Masaka DLG. This was based on the hypothesis that contract documentation as a component of contract management has a significant association with and influence onto service delivery. The research was carried out in Masaka DLG. Out of the study population of 140 respondents, a sample of 103 was selected. A response rate of 85.4% was realized for generalization of the research results. The data was collected using self-administered questionnaires. Basing on the objective of the study, descriptive, correlation and regression analyses were carried out. The results indicated that the practice of contract documentation process is averagely existent in the operations of Masaka DLG procurement unit and is reported to have a very strong association with education service delivery at the district (r = 0.645) which is statistically significance (p ≤ 0.01). Additionally, the contract documentation process influences up to 41% of the changes in education service delivery at the district. Basing on these results therefore, it is recommended that the contract documentation processes in Masaka DLG be improved so that education service delivery can be enhanced in the district.
Keywords: Education Service Delivery; Contract; Service delivery; Contract documentation